Locus of Control Analysis in Improving Satisfaction and Performance of Sharia Bank’s Employee - Astri Ayu Purwati; Silvia Sari Sitompul; Wella Sandria; Tri Purnama Sari; Muhammad Luthfi Hamzah (Universitas Pendidikan Ganesha, 2023)
The issue of human resource performance in Islamic Banking is an important concern. Based on the KPI value of one of Islamic banking employees in Pekanbaru, there are several aspects of performance measurement that have not been met, especially from the work behavior assessment. This study aimed to determine the effect of locus of control on employee satisfaction and performance. This type of research is quantitative, where the sample in this study was 95 Islamic bank employees in Pekanbaru, which were taken using a total sampling technique. The data was collected through questionnaires and analyzed using the Structural Equation Modeling (SEM) with AMOS application. The results showed that Internal locus of control has a positive and significant effect on Job Satisfaction and employee performance. External locus of control does not affect Job Satisfaction or the performance of banking employees. Job Satisfaction has a positive and significant effect on Employee Performance, and also Job satisfaction in this study has found as a mediating variable between internal locus of control on employee performance, but not in the external locus of control. The implications of this research can be used by Islamic banking in Pekanbaru to develop more effective employee development strategies and programs, focusing on developing internal locus of control and increasing job satisfaction.